Enterprise Knowledge Infrastructures - Maier, Ronald; Hädrich, Thomas; Peinl, René (Springer Berlin Heidelberg : Imprint: Springer, 2009)
Success of an organization is increasingly dependent on its capability to create an environment in order to improve productivity of knowledge work. This book focuses on the concepts, models and technologies that are used to design and implement such an environment. It develops the vision of a modular, yet highly integrated enterprise knowledge infrastructure and presents an idealized architecture replete with current technologies and systems. The most important streams of technological development that are covered in the book are communication, collaboration, document and content management, e-learning, enterprise portals, business process management, information life cycle management, information retrieval and visualization, knowledge management, mobile computing, application and network infrastructure, Semantic Web and social software. It includes learning goals, exercises and case examples that help the reader to easily understand and practice the concepts. .